2017
DOI: 10.1097/shk.0000000000000799
|View full text |Cite
|
Sign up to set email alerts
|

Late Therapeutic Intervention with Antibiotics and Fluid Resuscitation Allows for a Prolonged Disease Course with High Survival in a Severe Murine Model of Sepsis

Abstract: Current animal models of sepsis often incorporate antibiotics to be consistent with clinical standards for treatment of patients in the ICU. However, such experimental intervention is commonly initiated very early after infectious insult, which likely blunts the progression of systemic inflammation and downstream pathology. The objective of this study was to establish an animal model of sepsis with delayed therapeutic intervention, allowing a longer disease course and downstream pathology, but still resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 32 publications
4
41
0
Order By: Relevance
“…We adapted our recently reported ICU-like model of sepsis to late middle-aged C57BL/6 mice (Steele et al, 2017) (16 months; equivalent to ~50-year-old human [Flurkey K et al, 2007]). Sepsis was induced by bolus injection of cecal slurry (CS) and therapeutic resuscitation with antibiotics and fluids was initiated at 12h and continued twice daily for five days (schematic provided in Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We adapted our recently reported ICU-like model of sepsis to late middle-aged C57BL/6 mice (Steele et al, 2017) (16 months; equivalent to ~50-year-old human [Flurkey K et al, 2007]). Sepsis was induced by bolus injection of cecal slurry (CS) and therapeutic resuscitation with antibiotics and fluids was initiated at 12h and continued twice daily for five days (schematic provided in Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to better model the clinical course of sepsis by addressing the above four factors, we induced sepsis by CS injection in late middle-aged mice, and used our ICU-like severe model of sepsis (Steele et al, 2017) which resulted in ~75% survival after an otherwise lethal insult. In the current study, using ex vivo force analysis, we found that middle-aged sepsis surviving mice exhibit a ~ 20% reduction of muscle force compared to non-sepsis controls up to 1 month after sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4D) (32). Imipenem was intraperitoneally administered four times every 12 h (q12h) as previously described, with minor modifications (33). Interestingly, a single dose (10 mg/kg) of AMPR-11, which was a 10-fold lower concentration when tested for in vivo toxicity, increased the survival rate by Ͼ60% in both Gram-positive bacteria (S. aureus) and Gram-negative bacteria (P. aeruginosa, K. pneumoniae, and A. baumannii) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because most Veh-treated controls (71.4%) died within 48 h post-sepsis induction, it was difficult to collect specimens for histological analysis. To further elucidate the pathophysiology, we plan to conduct a study that includes histologic examination using a newly established murine model of sepsis with a prolonged disease course and high survival rate 42 . Although we utilised decapitation for blood collection in our study, this procedure is not ideal.…”
Section: Discussionmentioning
confidence: 99%